On the Procedures for the Extraction and Isolation of Flavonoids Present in the Methanolic Extract of Leaves of Acanthospermum Hispidiumdc - R. T, Abe; T. I, Edewor-Kuponiyi (International Journal of Natural Sciences Research, 2014)
This paper presents the procedures of the extraction and isolation of flavonoids present in the methanolic leaf extract of Acanthospermum hispidium DC .The leaves of Acanthospermum hispidium dc was extracted with polar and non-polar solvents. The activecomponents (.i.e. flavonoids) were found in methanol, chloroform, ethyl acetate and n-butanol while methanol, chloroform, ethylacetate and n-butanol contained steroids. From the chromatographic analysis, it was observed that the component 1and 2 have RF values of 0.61 and 0.48. The identification of the components and the specific absorption band were determined by spectroscopic analysis.